Effect of Growth Medium On Presence of Mychorrizal Vesicular Arbuscular (MVA) In Rhizosphere of Paddy (Oryza sativa var. Aek sibundong) - Tadzkiroh - Nim: 11413047, Amah
MVA (Mychorrizal vesicular arbuscular) is an endomycorrhiza associated with rice plants to help increase nutrient uptake in the soil. The study was designed using a randomized block design with 4 treatments and 6 replications to see the variation of planting media on the number, type, percentage of MVA infection and its effect on rice crop (Oryza sativa var Aek Sibundong). The treatment of planting media used is soil (T), soil and fertilizer NPK (KNP), soil and compost (K), and soil, compost and fertilizer NPK (KNPK). Cultivation of rice plants is done by SRI (System of Rice Intensification) and drip system (drip system). Identification of spore count using wet screening and centrifugation technique, while percentage of MVA infection was done by Phillips method and Haymann (1970) modified by Laboratory of Forest Biotechnology IPB. The results were tested using ANOVA followed by advanced test using DMRT (Duncan Multiple Range Test) with 95% confidence level. Based on the results of the study, the number of spores and percentage of infection in each planting medium in each growth phase had no significant difference, except the percentage of MVA infection at the maturation stage. The highest number of spores in the vegetative, generative, and maturation phases was found in the K treatment with 105,5 spores, 106,7 spores, and 194,83 spores per 50 gram of planting medium. The percentage of MVA infections in the roots of rice plants during the vegetative phase and the highest maturation on treatment K with the value of 52.43% and 57.5%, while the highest percentage of infections during the generative phase was found in the KNPK treatment with a value of 43.17%. The types of spores found in rice planting medium consist of Glomus pansihalos, Glomus lacteum, Glomus multicaule, Scutellaspora scutata, Acaulospora foveata, Ambispora gerdemamii, and Gigaspora decipien. The number of MVA spores has a fairly strong correlation with wet weight, dry weight, and weight of dry rice harvesting grain with a Pearson correlation value of 0.978; 0.985; and 0.965. This shows that the treatment of planting media in the form of soil and compost shows the highest MVA and productivity with GKG (Grain Dry Milling) of 8.25 tons / ha / harvest.